2009
DOI: 10.4103/0256-4947.51817
|View full text |Cite
|
Sign up to set email alerts
|

The value of renal ultrasound in children with a first episode of urinary tract infection

Abstract: BACKGROUND:Urinary tract infection (UTI) is a common pediatric problem. Guidelines recommend obtaining a renal ultrasonogram (RUS) for young children after a first UTI. Our aim was to assess the value of routine RUS in the management of children hospitalized with a first episode of UTI.METHODS:We conducted a retrospective review of the medical records of 130 children 12 years of age or younger admitted with a first UTI. Children were excluded if they had a urinary tract abnormality before admission and/or had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 7 publications
2
22
1
Order By: Relevance
“…In our study, prevalence of VUR in children with a history of urinary tract infections was 50.8%, which is considerable compared to the similar studies ( 4 , 5 , 17 , 18 , 19 , 20 ); this confirmed the fact that of those children routinely presenting for investigation of reflux about half do not have reflux ( 10 ). Our finding demonstrates the importance of selection of patients that would very likely not have reflux on VCUG or RNC, thus eliminating unnecessary X-ray exposure.…”
Section: Discussionsupporting
confidence: 81%
“…In our study, prevalence of VUR in children with a history of urinary tract infections was 50.8%, which is considerable compared to the similar studies ( 4 , 5 , 17 , 18 , 19 , 20 ); this confirmed the fact that of those children routinely presenting for investigation of reflux about half do not have reflux ( 10 ). Our finding demonstrates the importance of selection of patients that would very likely not have reflux on VCUG or RNC, thus eliminating unnecessary X-ray exposure.…”
Section: Discussionsupporting
confidence: 81%
“…The application of harmonic ultrasound further enhanced the specificity of CeVUS in the diagnosis of VUR ( 11 ), making it a reliable diagnostic method in Europe ( 17 ). In the present study, 44/90 children (48.79%) and 65/178 PUUs (36.52%) were diagnosed as VUR positive using CeVUS, which is consistent with a previous study ( 18 ) and suggests that >50% of high-risk children were VUR negative. VCUG results for 2 children indicated that they were VUR negative, whereas CeVUS later revealed that they were positive for VUR.…”
Section: Discussionsupporting
confidence: 93%
“…3 Layla et al reports 50% sensitivity and 76.9% specificity. 5 In our study VUR was identified in 24.5% whereas in a larger series 3 VUR was identified in 41.7%. Other study reports 22% prevalence, 40% sensitivity, 76% specificity, 32% positive and 82% negative predictive value.…”
Section: Discussioncontrasting
confidence: 42%